Sodium-ion battery positive electrode precursor, preparation method and application thereof
Patent Information
- Application Number
- CN202410141639.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-31
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-01-31
Smart Images

Figure CN118005098B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure belongs to the technical field of sodium-ion batteries, and specifically relates to a sodium-ion battery positive electrode precursor, its preparation method and application. Background Art
[0002] Sodium-ion battery positive electrode materials mainly include oxides, polyanions, Prussian blue analogs, and organic types. Among them, layered transition metal oxides in the oxides are a type of sodium-ion battery positive electrode material with relatively high specific capacity, good stability, and simple preparation methods, and their precursors have attracted much attention due to their characteristics such as low cost, good uniformity, controllable process, simple preparation method, and excellent performance. Polycrystalline positive electrode materials have been increasingly studied due to their advantages of good processability, high capacity, and good cycling performance. However, there are many problems in the process of sintering the precursor into a polycrystalline material. It is relatively common that the precursor produces excessive gas at the end of sintering and during the cycling process, and is subjected to uneven stress, resulting in cracking, which affects the large-scale application of oxide-based sodium-ion battery positive electrode materials. Summary of the Invention
[0003] The present disclosure aims to at least solve one of the technical problems existing in the above-mentioned prior art. To this end, the present disclosure proposes a sodium-ion battery positive electrode precursor, its preparation method and application, which can prepare a precursor material with a loose interior and a compact exterior, effectively solving the cracking problem existing in the precursor stage during the synthesis and sintering processes, and providing a new process idea and synthesis method for solving the cracking problem of positive electrode materials.
[0004] According to one aspect of the present disclosure, a sodium-ion battery positive electrode precursor is proposed, and the chemical general formula of the sodium-ion battery positive electrode precursor is M y Cu x (OH)₂, wherein 0<y<1, 0<x<1, y+x=1, and M is selected from at least one of Li, K, Al, Ti, Cr, Mn, Fe, Co, Ni, Zn, Mg, Sn, Zr, Mo, Nb, Y, W, In, Ge and the like; the sodium-ion battery positive electrode precursor has a loose and porous inner core and a dense and compact outer shell covering the inner core. The density of the outer shell is greater than the density of the inner core.
[0005] In some embodiments of the present disclosure, the particle size D50 of the inner core is 2-20 μm, and the tap density is 0.4-0.8 g / cm 3 . Further, the particle size D50 of the inner core is 2-8 μm.
[0006] In some embodiments of the present disclosure, the particle size D50 of the sodium-ion battery positive electrode precursor is 7-25 μm, and the tap density is 1.0-1.5 g / cm 3Specific surface area is 5-80m² 2 / g. Further, the particle size D50 of the sodium-ion battery cathode precursor is 7-13 μm, and the tap density is 1.0-1.25 g / cm³. 3 Specific surface area is 5-60m² 2 / g. Furthermore, the specific surface area of the sodium-ion battery cathode precursor is 15-30 m² / g. 2 / g.
[0007] This disclosure also provides a method for preparing the sodium-ion battery cathode precursor, comprising the following steps:
[0008] S1: Add water and precipitant to the reactor, adjust the pH to 8-13, prepare the bottom liquid of the reactor, introduce inert gas, stir, heat and keep the temperature constant;
[0009] S2: Using a continuous process, a mixed metal salt solution containing M and Cu and a precipitant are added to the reactor in parallel streams. The pH is controlled at 9.5-12.0 and the stirring frequency is 30-60Hz to carry out a co-precipitation reaction. When the particle size D50 of the slurry in the co-precipitation reaction system reaches the preset value, the core is obtained and the continuous process is stopped.
[0010] S3: Based on step S2, the continuous process is changed to an intermittent process, and the mixed metal salt solution and precipitant are added in parallel to grow the shell. As the solid content of the slurry in the reactor increases, the particle size of the slurry reaches the target value, thus obtaining the sodium-ion battery cathode precursor.
[0011] The continuous process described in this disclosure refers to the continuous addition of reactants to the reactor and the continuous discharge of products from the reactor; the batch process refers to the continuous addition of reactants to the reactor, without discharge of products, and the solid content in the reactor is increased by controlling the discharge rate.
[0012] In some embodiments of this disclosure, the mixed metal salt solution is at least one of chloride solution, sulfate solution, nitrate solution, oxalate solution, citrate solution, carbonate solution or acetate solution.
[0013] In some embodiments of this disclosure, the concentration of the mixed metal salt solution is 0.1-2.5 mol / L. Further, the concentration of the mixed metal salt solution is 1.7-2.0 mol / L.
[0014] In some embodiments of this disclosure, in step S1, 6. a complexing agent is added to the reaction vessel bottom liquid in step S1 and the co-current liquid in step S2; the concentration of the complexing agent is 0-6 g / L. Further, the complexing agent is ammonia water.
[0015] In some embodiments of this disclosure, the precipitant is liquid alkali, and the concentration of the liquid alkali is 5-12 mol / L.
[0016] In some embodiments of this disclosure, in step S1, the heating temperature is 40-85°C.
[0017] In some embodiments of this disclosure, in step S2, the pH of the coprecipitation reaction is controlled to be 10.0-12.0.
[0018] In some embodiments of this disclosure, in step S2, the stirring frequency of the coprecipitation reaction is controlled to be 50-60 Hz.
[0019] In some embodiments of this disclosure, in step S3, when the solid content of the slurry in the reactor increases to 200-800 g / L, the pH of the reaction system is lowered before growth continues. Lowering the pH can reduce the number of nuclei, promote the growth of secondary precursor particles, and prevent the formation of small particles. Further, the solid content of the slurry in the reactor is 400-600 g / L. Further, in step S3, the pH of the reaction system is lowered to 9.0-10.0.
[0020] In some embodiments of this disclosure, in step S2, the influent flow rate of the mixed metal salt solution is controlled to be 8-20 L / h. Further, in step S2, the influent flow rate of the mixed metal salt solution is controlled to be 15-20 L / h.
[0021] In some embodiments of this disclosure, in step S3, the purging flow rate in the batch process is controlled to be 8-20 L / h. In some embodiments of this disclosure, in step S3, when the solid content of the slurry in the reactor increases to 200-800 g / L, the influent flow rate of the mixed metal salt solution is reduced before growth continues. Reducing the influent flow rate slows down the reaction process, ensuring slow growth of the precursor secondary particles and improving the shell density. Further, in step S3, the influent flow rate of the mixed metal salt solution is reduced to 8-15 L / h.
[0022] In some embodiments of this disclosure, in step S3, when the solid content of the slurry in the reactor increases to 200-800 g / L, the stirring frequency of the reactor is reduced before growth continues. Reducing the stirring rate can prevent the formation of small particles. Further, in step S3, the stirring frequency of the reactor is reduced to 40-50 Hz.
[0023] This disclosure also provides a sodium-ion battery cathode material, which is prepared by reacting the aforementioned sodium-ion battery cathode precursor with a sodium source.
[0024] This disclosure also provides a sodium-ion battery, the raw materials of which include the aforementioned sodium-ion battery cathode material.
[0025] According to the embodiments of this disclosure, at least the following beneficial effects are achieved:
[0026] 1. This disclosure employs a two-step process combining continuous and batch methods. First, a co-precipitation reaction is performed using a continuous process, primarily involving nucleation. A higher pH value increases the number of nuclei, and combined with a higher stirring frequency, this synthesizes precursor cores with larger specific surface areas and lower tap density. Then, a batch process is used for concentration to increase solid content and promote precursor growth. Due to the increased concentration and supersaturation in the reactor, effective collisions increase, resulting in a dense and compact outer shell. If only a continuous process is used to prepare the precursor, the resulting morphology and structure are relatively uniform, and it is generally difficult to obtain a core-shell structured precursor. However, this disclosure, by employing both continuous and batch processes, can effectively control the precursor structure, the size of the core, and the thickness of the outer shell.
[0027] 2. This disclosure can strictly control the morphology, particle size, primary particles, secondary particles, elemental composition, specific surface area, tap density, and compactness of the precursor; at the same time, it can also effectively control the looseness of the core and the compactness of the shell.
[0028] 3. This invention breaks with the traditional synthesis approach. Traditional methods for addressing cracking at the precursor end mostly involve preparing radial structures, i.e., a structure that is tight inside and loose outside. However, due to the relatively dense interior, cracking can still occur. In contrast, this invention prepares a structure that is loose inside and tight outside, which can effectively avoid cracking caused by stress.
[0029] 4. The precursor prepared in this disclosure has a structure that is similar to a hollow structure but not a hollow structure. It has an internal framework that will not cause the material structure to collapse. The core has many hollow channels, which provide ion transport channels for the material, improve the diffusion rate, and enhance the rate performance. Attached Figure Description
[0030] The present disclosure will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0031] Figure 1 This is a SEM image of the precursor of Embodiment 1 of this disclosure;
[0032] Figure 2 This is a CP diagram of the precursor of Embodiment 1 of this disclosure;
[0033] Figure 3 This is a CP diagram of the precursor of Comparative Example 1 of this disclosure;
[0034] Figure 4 This is a CP diagram of the precursor of Comparative Example 2 of this disclosure;
[0035] Figure 5 This is the process flow diagram disclosed herein. Detailed Implementation
[0036] The following will describe the concept and technical effects of this disclosure clearly and completely with reference to the embodiments, so as to fully understand the purpose, features and effects of this disclosure.
[0037] Example 1
[0038] This embodiment prepares a sodium-ion battery cathode precursor Ni with a loose inner core and a tight outer core. 0.2 Mn 0.45 Fe 0.20 Cu 0.15 (OH)₂ has a loose, porous core and a dense, compact outer shell. The specific process is as follows:
[0039] (1) Preparation of metal solution: Weigh the corresponding nickel sulfate, manganese sulfate, ferrous sulfate and copper sulfate raw materials according to the molar ratio of Ni:Mn:Fe:Cu of 0.2:0.45:0.20:0.15 to prepare a mixed metal salt solution with a concentration of 2mol / L;
[0040] (2) Prepare the bottom liquid of the reaction vessel: add 1 / 3 of the volume of pure water and an appropriate amount of liquid alkali to the reaction vessel, adjust the pH value to 10.5, set the ammonia water to 0g / L (ammonia-free), set the reaction temperature to 70℃, introduce nitrogen gas, turn on the stirrer, and set the stirring frequency to 60Hz.
[0041] (3) Continuous synthesis of the nucleus: A mixed metal salt solution and a 10 mol / L liquid alkali were slowly and concurrently introduced into the reactor for a nucleation reaction (co-precipitation reaction). The flow rate of the mixed metal salt solution was 15 L / h, the pH of the reaction system was controlled at 10.5, and the stirring frequency was 60 Hz. When the particle size D50 of the slurry in the reaction system was 5 μm, a precursor nucleus with a large specific surface area and low compactness was synthesized, and the continuous reaction was stopped. The tap density of the nucleus was measured to be 0.76 g / cm³. 3 ;
[0042] (4) Intermittent concentration-solidification method: When the particle size D50 of the slurry in step (3) reaches 5 μm, the method is changed to intermittent based on step (3). The effluent flow rate in the reactor is 15 L / h, and the mixed metal salt solution is continuously introduced for growth. As the reaction proceeds, the solid content increases. When the solid content increases to 300 g / L, the pH value is reduced to 9.5, and the influent flow rate of the mixed metal salt solution is maintained at 15 L / h. At the same time, according to the experimental design, the stirring frequency is reduced to 47 Hz, and the influent flow rate of the mixed metal salt solution is controlled according to the thickness of the shell. Finally, Ni with good sphericity, high tap density, and low specific surface area is synthesized with a loose inner and tight outer structure. 0.2 Mn 0.45 Fe 0.20 Cu 0.15(OH)2 precursor, with a precursor particle size D50 of 10 μm.
[0043] Figure 2 The diagram shows the CP diagram of the precursor in this embodiment. It can be seen that the interior of the particles is relatively loose, the exterior is relatively compact, the shell structure has almost no gaps, and the boundary between the core and the shell is relatively clear.
[0044] Example 2
[0045] This embodiment prepares a sodium-ion battery cathode precursor Ni with a loose inner core and a tight outer core. 0.25 Mn 0.40 Fe 0.25 Cu 0.10 (OH)₂ has a loose, porous core and a dense, compact outer shell. The specific process is as follows:
[0046] (1) Preparation of metal solution: Weigh the corresponding nickel sulfate, manganese sulfate, ferrous sulfate and copper sulfate raw materials according to the molar ratio of Ni:Mn:Fe:Cu of 0.25:0.40:0.25:0.10 to prepare a mixed metal salt solution with a concentration of 2mol / L.
[0047] (2) Prepare the bottom liquid of the reaction vessel: add 1 / 3 of the volume of pure water and an appropriate amount of liquid alkali to adjust the pH value to 10.2, set the ammonia water to 0g / L (ammonia-free), set the reaction temperature to 70℃, introduce nitrogen gas, turn on the stirrer, and set the stirring frequency to 60Hz.
[0048] (3) Continuous synthesis of the nucleus: A mixed metal salt solution and a 10 mol / L liquid alkali were slowly and concurrently introduced into the reactor for a nucleation reaction (co-precipitation reaction). The flow rate of the mixed metal salt solution was 20 L / h, the pH of the reaction system was controlled at 10.5, and the stirring frequency was 60 Hz. When the particle size D50 of the slurry in the reaction system was 4 μm, a precursor nucleus with a large specific surface area and low compactness was synthesized, and the continuous reaction was stopped. The tap density of the nucleus was measured to be 0.74 g / cm³. 3 ;
[0049] (4) Intermittent Concentration-Solidification Method: When the particle size D50 of the slurry in step (3) reaches 4 μm, the method is changed to intermittent method based on step (3). The effluent flow rate in the reactor is 20 L / h, and the mixed metal salt solution is continuously introduced for growth. As the reaction proceeds, the solid content increases. When the solid content increases to 450 g / L, the pH value is reduced to 9.7, the influent flow rate of the mixed metal salt solution is reduced to 15 L / h, and the effluent flow rate in the reactor is reduced to 15 L / h. At the same time, according to the experimental design, the stirring frequency is reduced to 47 Hz, and the influent flow rate of the mixed metal salt solution is controlled according to the thickness of the shell. Finally, Ni with good sphericity, high tap density, and low specific surface area is synthesized with a loose inner and tight outer structure. 0.25 Mn0.40 Fe 0.25 Cu 0.10 (OH)2 precursor, with a precursor particle size D50 of 8 μm.
[0050] Example 3
[0051] This embodiment prepares a sodium-ion battery cathode precursor Ni with a loose inner core and a tight outer core. 0.22 Mn 0.48 Fe 0.20 Cu 0.10 (OH)₂ has a loose, porous core and a dense, compact outer shell. The specific process is as follows:
[0052] (1) Preparation of metal solution: Weigh the corresponding nickel sulfate, manganese sulfate, ferrous sulfate and copper sulfate raw materials according to the molar ratio of Ni:Mn:Fe:Cu of 0.22:0.48:0.20:0.10 to prepare a mixed metal salt solution with a concentration of 1.7mol / L;
[0053] (2) Prepare the bottom liquid of the reaction vessel: add 1 / 3 of the volume of pure water and appropriate amount of liquid alkali to the reaction vessel, adjust the pH value to 10.2, set the ammonia water to 0.5g / L, set the reaction temperature to 70℃, introduce nitrogen gas, turn on the stirrer, and set the stirring frequency to 60Hz.
[0054] (3) Continuous synthesis of the nucleus: A mixed metal salt solution, a 10 mol / L liquid alkali solution, and a 0.5 g / L ammonia solution were slowly and concurrently introduced into the reactor for a nucleation reaction (co-precipitation reaction). The flow rate of the mixed metal salt solution was 20 L / h, the pH of the reaction system was controlled at 10.4, and the stirring frequency was 60 Hz. When the particle size D50 of the slurry in the reaction system was 6 μm, a precursor nucleus with a large specific surface area and low compactness was synthesized, and the continuous reaction was stopped. The tap density of the nucleus was measured to be 0.78 g / cm³. 3 ;
[0055] (4) Intermittent Concentration-Solidification Method: When the particle size D50 of the slurry in step (3) reaches 6 μm, the method is changed to intermittent method based on step (3). The effluent flow rate in the reactor is 20 L / h, and the mixed metal salt solution is continuously introduced for growth. As the reaction proceeds, the solid content increases. When the solid content increases to 450 g / L, the pH value is reduced to 9.6. The influent flow rate of the mixed metal salt solution is maintained at 20 L / h, and the effluent flow rate in the reactor is 20 L / h. At the same time, according to the experimental design, the stirring frequency is reduced to 45 Hz. The influent flow rate of the mixed metal salt solution is controlled according to the thickness of the shell. Finally, Ni with good sphericity, high tap density, and low specific surface area is synthesized with a loose inner and tight outer structure. 0.22 Mn 0.48 Fe 0.20 Cu 0.10(OH)2 precursor, with a precursor particle size D50 of 10 μm.
[0056] Example 4
[0057] This embodiment prepares a sodium-ion battery cathode precursor Ni with a loose inner core and a tight outer core. 0.15 Mn 0.45 Fe 0.20 Cu 0.10 (OH)₂ has a loose, porous core and a dense, compact outer shell. The specific process is as follows:
[0058] (1) Preparation of metal solution: Weigh the corresponding nickel sulfate, manganese sulfate, ferrous sulfate and copper sulfate raw materials according to the molar ratio of Ni:Mn:Fe:Cu of 0.15:0.45:0.20:0.10 to prepare a mixed metal salt solution with a concentration of 1.8 mol / L;
[0059] (2) Prepare the bottom liquid of the reaction vessel: add 1 / 3 of the volume of pure water and appropriate amount of liquid alkali to the reaction vessel, adjust the pH value to 10.0, set the ammonia water to 1.0 g / L, set the reaction temperature to 65℃, introduce nitrogen gas, turn on the stirrer, and set the stirring frequency to 55 Hz.
[0060] (3) Continuous synthesis of the nucleus: A mixed metal salt solution, 10 mol / L liquid alkali, and 1.0 g / L ammonia solution were slowly and concurrently introduced into the reactor for a nucleation reaction (co-precipitation reaction). The flow rate of the mixed metal salt solution was 16 L / h, the pH of the reaction system was controlled at 10.0, and the stirring frequency was 50 Hz. When the particle size D50 of the slurry in the reaction system was 7 μm, a precursor nucleus with a large specific surface area and low compactness was synthesized, and the continuous reaction was stopped. The tap density of the nucleus was measured to be 0.73 g / cm³. 3 ;
[0061] (4) Intermittent Concentration-Solidification Method: When the particle size D50 of the slurry in step (3) reaches 7 μm, the method is changed to intermittent method based on step (3). The effluent flow rate in the reactor is 16 L / h, and the mixed metal salt solution is continuously introduced for growth. As the reaction proceeds, the solid content increases. When the solid content increases to 500 g / L, the pH value is reduced to 9.5. The influent flow rate of the mixed metal salt solution is kept at 16 L / h, and the effluent flow rate in the reactor is kept at 16 L / h. At the same time, the stirring frequency is kept at 50 Hz. The influent flow rate of the mixed metal salt solution is controlled according to the thickness of the shell. Finally, Ni with good sphericity, high tap density, and low specific surface area is synthesized. 0.15 Mn 0.45 Fe 0.20 Cu 0.10 (OH)2 precursor, with a precursor particle size D50 of 12 μm.
[0062] Example 5
[0063] This embodiment prepares a sodium-ion battery cathode precursor Ni with a loose inner core and a tight outer core. 0.2 Mn 0.3 Fe 0.3 Cu 0.2 (OH)₂ has a loose, porous core and a dense, compact outer shell. The specific process is as follows:
[0064] (1) Preparation of metal solution: Weigh the corresponding nickel sulfate, manganese sulfate, ferrous sulfate and copper sulfate raw materials according to the molar ratio of Ni:Mn:Fe:Cu of 0.2:0.3:0.30:0.20 to prepare a mixed metal salt solution with a concentration of 2.0 mol / L;
[0065] (2) Prepare the bottom liquid of the reaction vessel: add 1 / 3 of the volume of pure water and an appropriate amount of liquid alkali to the reaction vessel, adjust the pH value to 11.0, set the reaction temperature to 75℃, introduce nitrogen gas, turn on the stirrer, and set the stirring frequency to 60Hz.
[0066] (3) Continuous synthesis of the nucleus: A mixed metal salt solution and a 10 mol / L liquid alkali were slowly and concurrently introduced into the reactor for a nucleation reaction (co-precipitation reaction). The flow rate of the mixed metal salt solution was 16 L / h, the pH of the reaction system was controlled at 11.0, and the stirring frequency was 55 Hz. When the particle size D50 of the slurry in the reaction system was 6 μm, a precursor nucleus with a large specific surface area and low compactness was synthesized, and the continuous reaction was stopped. The tap density of the nucleus was measured to be 0.72 g / cm³. 3 ;
[0067] (4) Intermittent Concentration-Solidification Method: When the particle size D50 of the slurry in step (3) reaches 6 μm, the method is changed to intermittent method based on step (3). The effluent flow rate in the reactor is 16 L / h, and the mixed metal salt solution is continuously introduced for growth. As the reaction proceeds, the solid content increases. When the solid content increases to 400 g / L, the pH value is reduced to 9.5, the influent flow rate of the mixed metal salt solution is reduced to 10 L / h, and the effluent flow rate in the reactor is reduced to 10 L / h. At the same time, the stirring frequency is reduced to 42 Hz. The influent flow rate of the mixed metal salt solution is controlled according to the thickness of the shell. Finally, Ni with good sphericity, high tap density, and low specific surface area is synthesized. 0.2 Mn 0.3 Fe 0.3 Cu 0.2 (OH)2 precursor, with a precursor particle size D50 of 9 μm.
[0068] Example 6
[0069] This embodiment prepares a sodium-ion battery cathode precursor Ni with a loose inner core and a tight outer core. 0.2 Mn 0.3 Fe0.3 Cu 0.15 Zn 0.05 (OH)₂ has a loose, porous core and a dense, compact outer shell. The specific process is as follows:
[0070] (1) Preparation of metal solution: Weigh the corresponding nickel sulfate, manganese sulfate, ferrous sulfate, copper sulfate and zinc sulfate raw materials according to the molar ratio of Ni:Mn:Fe:Cu:Zn of 0.2:0.3:0.30:0.15:0.05 to prepare a mixed metal salt solution with a concentration of 1.85mol / L;
[0071] (2) Prepare the bottom liquid of the reaction vessel: add 1 / 3 of the volume of pure water and appropriate amount of liquid alkali to the reaction vessel, adjust the pH value to 11.3, set the reaction temperature to 60℃, set the ammonia water to 0.5g / L, introduce nitrogen gas, turn on the stirring, and set the stirring frequency to 60Hz.
[0072] (3) Continuous synthesis of the nucleus: A mixed metal salt solution, a 10 mol / L liquid alkali solution, and a 0.5 g / L ammonia solution were slowly and concurrently introduced into the reactor for a nucleation reaction (co-precipitation reaction). The flow rate of the mixed metal salt solution was 18 L / h, the pH of the reaction system was controlled at 11.5, and the stirring frequency was 52 Hz. When the particle size D50 of the slurry in the reaction system was 4 μm, a precursor nucleus with a large specific surface area and low compactness was synthesized, and the continuous reaction was stopped. The tap density of the nucleus was measured to be 0.79 g / cm³. 3 ;
[0073] (4) Intermittent Concentration-Solidification Method: When the particle size D50 of the slurry in step (3) reaches 4 μm, the method is changed to intermittent method based on step (3). The effluent flow rate in the reactor is 18 L / h, and the mixed metal salt solution is continuously introduced for growth. As the reaction proceeds, the solid content increases. When the solid content increases to 500 g / L, the pH value is reduced to 10.0, the influent flow rate of the mixed metal salt solution is reduced to 10 L / h, and the effluent flow rate in the reactor is reduced to 10 L / h. At the same time, the stirring frequency is reduced to 45 Hz. The influent flow rate of the mixed metal salt solution is controlled according to the thickness of the shell. Finally, Ni with good sphericity, high tap density, and low specific surface area is synthesized with a loose inner and tight outer structure. 0.2 Mn 0.3 Fe 0.3 Cu 0.15 Zn 0.05 (OH)2 precursor, with a precursor particle size D50 of 8 μm.
[0074] Comparative Example 1
[0075] This comparative example prepared a sodium-ion battery cathode precursor Ni. 0.2 Mn 0.45 Fe 0.20 Cu0.15 The difference between (OH)2 and Example 1 is that the batch process was not used in the later stages. The entire process was synthesized using a continuous process under the same conditions as in Example 1. The specific process is as follows:
[0076] (1) Preparation of metal solution: Weigh the corresponding nickel sulfate, manganese sulfate, ferrous sulfate and copper sulfate raw materials according to the molar ratio of Ni:Mn:Fe:Cu of 0.2:0.45:0.20:0.15 to prepare a mixed metal salt solution with a concentration of 2mol / L;
[0077] (2) Prepare the bottom liquid of the reaction vessel: add 1 / 3 of the volume of pure water and an appropriate amount of liquid alkali to the reaction vessel, adjust the pH value to 10.5, set the ammonia water to 0g / L (ammonia-free), set the reaction temperature to 70℃, introduce nitrogen gas, turn on the stirrer, and set the stirring frequency to 60Hz.
[0078] (3) Continuous synthesis: A mixed metal salt solution and a 10 mol / L liquid alkali solution were slowly and concurrently introduced into the reactor for a nucleation reaction (co-precipitation reaction). The flow rate of the mixed metal salt solution was 15 L / h. The pH of the reaction system was controlled at 10.5, and the stirring frequency was 60 Hz. When the particle size D50 of the slurry was 5 μm, the pH was gradually reduced to 9.5, and the stirring frequency was reduced to 47 Hz to continue the reaction, yielding Ni with a particle size D50 of 10 μm. 0.2 Mn 0.45 Fe 0.20 Cu 0.15 (OH)2 precursor.
[0079] Figure 3 The figure shows the CP diagram of the precursor in this comparative example. It can be seen that the overall structure of the precursor is relatively loose and does not form a core-shell structure that is loose inside and tight outside.
[0080] Comparative Example 2
[0081] This comparative example prepared a sodium-ion battery cathode precursor Ni. 0.2 Mn 0.45 Fe 0.20 Cu 0.15 The difference between (OH)2 and Example 1 is that the entire process uses a batch process. The whole process is synthesized under the same conditions as in Example 1 using a batch process. The specific process is as follows:
[0082] (1) Preparation of metal solution: Weigh the corresponding nickel sulfate, manganese sulfate, ferrous sulfate and copper sulfate raw materials according to the molar ratio of Ni:Mn:Fe:Cu of 0.2:0.45:0.20:0.15 to prepare a mixed metal salt solution with a concentration of 2mol / L;
[0083] (2) Prepare the bottom liquid of the reaction vessel: add 1 / 3 of the volume of pure water and an appropriate amount of liquid alkali to the reaction vessel, adjust the pH value to 10.5, set the ammonia water to 0g / L (ammonia-free), set the reaction temperature to 70℃, introduce nitrogen gas, turn on the stirrer, and set the stirring frequency to 60Hz.
[0084] (3) Batch synthesis: A mixed metal salt solution and a 10 mol / L liquid alkali were slowly and concurrently introduced into the reactor for a co-precipitation reaction. The flow rate of the mixed metal salt solution was 15 L / h, the pH of the reaction system was controlled at 10.5, the stirring frequency was 60 Hz, and the effluent flow rate from the reactor was 15 L / h. As the reaction proceeded, the solid content increased. When the solid content increased to 300 g / L, the pH value was lowered to 9.5, the influent flow rate of the mixed metal salt solution was maintained at 15 L / h, the stirring frequency was reduced to 47 Hz, and the reaction continued to obtain Ni with a particle size D50 of 10 μm. 0.2 Mn 0.45 Fe 0.20 Cu 0.15 (OH)2 precursor.
[0085] Figure 4 The figure shows the CP diagram of the precursor in this comparative example. It can be seen that the overall structure of the precursor is relatively compact, without forming a core-shell structure that is loose inside and tight outside.
[0086] Table 1. Physicochemical data of the precursors obtained from the examples and comparative examples.
[0087] project <![CDATA[Tap density (g / cm 3 )]]> <![CDATA[Apparent density (g / cm 3 )]]> <![CDATA[Specific surface area (m 2 / g)]]> Example 1 1.20 0.75 18 Example 2 1.15 0.82 20 Example 3 1.22 0.91 22 Example 4 1.24 0.84 25 Example 5 1.18 0.96 27 Example 6 1.23 0.93 16 Comparative Example 1 0.95 0.73 36 Comparative Example 2 1.30 1.05 12
[0088] Test case
[0089] The sodium-ion battery positive electrode precursors prepared in the above examples and comparative examples are used to make sodium-ion battery positive electrode materials and positive electrode sheets. These are then assembled with negative electrode sheets, separators, and electrolytes to obtain sodium-ion batteries.
[0090] The preparation method of sodium-ion battery cathode material includes: mixing the precursor materials obtained in each embodiment and comparative example with a sodium source, performing a mixing treatment, wherein the mass ratio of Na:Me is 1.05:1, and then performing a high-temperature sintering treatment, with a sintering temperature of 930℃ and a sintering time of 10h, to obtain sodium-ion battery cathode material.
[0091] The preparation method of the positive electrode sheet includes: weighing and mixing the above-mentioned sodium-ion battery positive electrode material, conductive carbon black, and vinylidene fluoride in a mass ratio of 80:10:10, and then uniformly mixing them in an N-methylpyrrolidone solution. The mixture is then made into a slurry, coated onto aluminum foil, vacuum dried, and after drying, cut and punched into positive electrode sheets with a diameter of 12 mm.
[0092] The preparation method of sodium-ion battery includes: using a metallic sodium sheet as the negative electrode, using a 1 mol / L NaPF6 / polycarbonate (PC): ethylene carbonate (EC): dimethyl carbonate (DMC) (volume ratio of 1:1:1) + 5% FEC solution as the electrolyte, using glass fiber as the separator, and assembling the battery into a button cell in an argon glove box.
[0093] Electrochemical performance tests were conducted on the above sodium-ion batteries under the following conditions: charge-discharge tests were performed at a voltage range of 1.5-4.1V and a charge-discharge rate of 0.1C. The initial charge-discharge specific capacity and initial coulombic efficiency were obtained, and the test results are shown in Table 2.
[0094] Table 2 Electrochemical performance of examples and comparative examples
[0095]
[0096]
[0097] As shown in Tables 1 and 2, compared to the continuous process alone, the precursor prepared by combining the continuous and batch processes of this disclosure has a higher tap density and a lower specific surface area, which can reduce the problem of increased residual sodium on the surface caused by excessively high specific surface area. In terms of electrochemical performance, the precursor prepared by this process has better rate performance than the materials prepared by either the continuous process alone or the batch process alone.
[0098] The embodiments of this disclosure have been described in detail above with reference to the accompanying drawings. However, this disclosure is not limited to the above embodiments, and various changes can be made within the scope of knowledge possessed by those skilled in the art without departing from the spirit of this disclosure. Furthermore, the embodiments of this disclosure and the features thereof can be combined with each other unless otherwise specified.
Claims
1. A sodium-ion battery positive electrode precursor, characterized in that, The chemical general formula of the sodium-ion battery positive electrode precursor is M y Cu x (OH)₂, where 0<y<1, 0<x<1, y+x=1, M is selected from at least one of Li, K, Al, Ti, Cr, Mn, Fe, Co, Ni, Zn, Mg, Sn, Zr, Mo, Nb, Y, W, In, and Ge; the sodium-ion battery positive electrode precursor has a loose and porous inner core and a dense and compact outer shell coated on the inner core; The method for preparing the sodium-ion battery cathode precursor includes the following steps: S1: Add water and precipitant to the reactor, adjust the pH to 8-13, prepare the bottom liquid of the reactor, introduce inert gas, stir, heat and keep the temperature constant; S2: Using a continuous process, a mixed metal salt solution containing M and Cu and a precipitant are added to the reactor in parallel streams. The pH is controlled at 9.5-12.0 and the stirring frequency is 30-60Hz to carry out a co-precipitation reaction. When the particle size D50 of the slurry in the co-precipitation reaction system reaches the preset value, the core is obtained and the continuous process is stopped. S3: Based on step S2, the continuous process is changed to an intermittent process, and the mixed metal salt solution and precipitant are added in parallel to grow the shell. As the solid content of the slurry in the reactor increases, the particle size of the slurry reaches the target value, thus obtaining the sodium-ion battery cathode precursor. In step S3, when the solid content of the slurry in the reactor increases to 200-800 g / L, the pH of the reaction system is lowered and growth continues. In step S3, when the solid content of the slurry in the reactor increases to 200-800 g / L, the stirring frequency of the reactor is reduced and growth continues.
2. The sodium-ion battery positive electrode precursor according to claim 1, characterized in that, The kernel has a particle size D50 of 2-20 μm and a tap density of 0.4-0.8 g / cm³. 3 .
3. The sodium-ion battery positive electrode precursor according to claim 1, characterized in that, The sodium-ion battery cathode precursor has a particle size D50 of 7-25 μm and a tap density of 1.0-1.5 g / cm³. 3 Specific surface area is 5-80m² 2 / g.
4. The sodium-ion battery positive electrode precursor according to claim 1, characterized in that, A complexing agent is added to the bottom liquid of the reaction vessel in step S1 and to the co-current liquid in step S2; the concentration of the complexing agent is 0-6 g / L.
5. The sodium-ion battery positive electrode precursor according to claim 1, characterized in that, In step S2, the inlet flow rate of the mixed metal salt solution is controlled to be 8-20 L / h.
6. The sodium-ion battery positive electrode precursor according to claim 5, characterized in that, In step S3, when the solid content of the slurry in the reactor increases to 200-800 g / L, the flow rate of the mixed metal salt solution is reduced and growth continues.
7. The application of the sodium-ion battery positive electrode precursor as described in any one of claims 1-3 in sodium-ion batteries.
Citation Information
Patent Citations
Nickel-containing precursor, nickel-containing composite material, and preparation methods and applications of nickel-containing precursor and nickel-containing composite material
CN112624208A
Monocrystal positive electrode material precursor and preparation method and application thereof
CN116730405A
